PSO modelling and PID controlled of automatic fish feeder system - W Mahmud, Wan Muhammad Azlan (2020)
Automatic fish feeding system is an electronic device that is designed to distribute fish pellets at particular time with maximum speed regulation. There are three (3) main parts in the system which are storage, dispenser and distribution parts. A problem has been reported that the distribution part was not performed at the required speed. The main objective of this study is to improve the performance of fish feeding system by using PID controller through ARX modelling. In this study, raw data at distribution part with speed of 130 rpm, 160 rpm, 190 rpm, 220 rpm and 250 rpm were extracted and used to determine ARX equation parameters as transfer function by using PSO algorithm to optimize ARX model parameter. Validation tests used was residual analysis. The best transfer function was then used as a modelling plant in the simulation process with PID controller to determine the optimum PID parameters. Finally, implementation of a PID controller into real time system was done to verify whether this system improved or not. The PSO analysis showed that the best ARX model was at 190 rpm speed because of well superimposed predicted model with the actual system. The lowest normalized output MSE value is 0.0042015 , the lowest convergence output error value is 0.0040886, the stable pole zero map and correlation test verify the accuracy of the model reaching a 95% confidence level. ARX model parameters obtained using the PSO algorithm are two inputs ( , ) and two outputs ( , ). The input parameter obtained is (− 0.3391, − 0.4329) while the output parameter is (− 0.06498, − 0.08334). The optimum PID parameter value obtained by the auto tune method is = − 3.4854, = − 50.2207 and = 0.05815. In conclusion, the PID controller successfully improved the performance of the fish feeding system with the highest percentage of speed change of 92.59%.